Analysis of audible acousto-optic signals for detection of low vibration signal using 1mW laser / Muhammad Adib Akram Mohdami Norashid - Mohdami Norashid, Muhammad Adib Akram (2016)
A new laser-safe optical microphone is designed to detect various changes in acoustooptic effect occurring due to small vibrating surfaces. The problem with the current optical microphone is that it uses Class III lasers in the range of 6 mW to 28 mW which is hazardous to the public. This device consists of a Class II 1 mW laser beam, which act as a sensing element directed to photo detector via a series of Fourier lenses followed with electronic circuit.